Moral Education in Wasiat Renungan Masa by TGKH. Muhammad Zainuddin Abdul Madjid: An Examination of Ibn Miskawaih's Philosophy - Atsani, Lalu Gede Muhammad Zainuddin; Nasri, Ulyan; Walad, Muzakkir; Yakin, Hakkul; Zulkifli, Muh. (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This research discusses the moral education found in “Wasiat Renungan Masa” by TGKH. Muhammad Zainuddin Abdul Madjid through an examination of Ibn Miskawaih's moral philosophy. The aim of this study is focused on understanding moral education within “Wasiat Renungan Masa” by using the lens of Ibn Miskawaih's moral philosophy. The research method employed is a literature analysis, which includes the identification of research objectives, data identification, data collection, data selection, data extraction, thematic analysis, comparison, contrast, pattern identification, as well as research conclusions and implications. The results of this study indicate that moral education in